Salt transport in the South Platte river system: modeling, controlling factors, and management strategies - Hocking, Craig, author; Bailey, Ryan T., advisor; Ronayne, Michael J., committee member; Niemann, Jeffrey D., committee member (Colorado State University. Libraries, 2021)
Increasing salinity poses a severe threat to urban and agricultural areas. Excess salt can accumulate in soils and groundwater, thereby impacting crop growth and productivity. This thesis aims to quantify the influence of the driving forces behind salt transport in Colorado's agro-urban South Platte River network, which has an approximate drainage area of 24,300 mi2 (62,937 km2), and investigates possible mitigation strategies to reduce salinity levels in both urban and agricultural river reaches. For this study, a one-dimensional in-river salt transport model was developed for the South Platte River system utilizing StateMod (Colorado's Division of Water Resources water allocation model) to simulate streamflow. The model accounts for multiple inputs and outputs of salt within the river network, including tributaries, wastewater treatment plants, road salt, runoff return flows from irrigation, and groundwater discharge, the latter from interpolated groundwater concentration maps generated from sampling data provided by the Agricultural Water Quality database. These concentration data are combined with the StateMod-simulated streamflow to simulate salt flow through the river network. The flow and salt models were run on a monthly basis over five years between 2002 and 2006. Based on Nash-Sutcliffe Coefficient of Efficiency (NSCE) statistics for the flow and salt models, 85% of the flow model's monthly NSCE values and approximately 68% of the salt model's monthly NSCE values fell within the acceptable range of zero to one. A global sensitivity analysis was implemented to determine the controlling factors behind salt transport in the river system. Two different scenarios were run: a reach-to-reach sensitivity study where the South Platte River was divided into five different reaches, and a seasonal sensitivity study performed over the entire South Platte River for spring (March to May), summer (June to August), fall (September to November), and winter (December to February). For urban areas located in the upstream region of the basin, controlling factors include wastewater treatment plant (WWTP) effluent concentration, salt in urban return flows, the initial concentration of salinity in upstream river water, and road salt loading. For agriculture areas located in the downstream region of the basin, controlling factors include the WWTP effluent concentration, salt in urban return flows, salt in agricultural return flows, and road salt loading, indicating the influence of upstream salinity loadings on downstream river water. Based on the sensitivity studies results, an assessment of potential management practices (MPs) was carried out for both urban and agricultural reaches. A total of 256 different MP trials were run each month. The final MP results were then calculated as the averages of the individual monthly results. A point system was assigned to help rank the trials by how efficient they were at reducing salinity levels. For the urban region, the most efficient MP during the spring and summer months is to reduce WWTP effluent concentration by 35%, resulting in a salinity concentration of 340 mg/L, a decrease of 17% from the baseline value. During the fall and winter months, the most efficient MP is to reduce road salt by 35%, resulting in a salinity concentration of 730 mg/L, a decrease of 19% from the baseline value. For agricultural areas, very few MP combinations achieve an in-river salinity concentration less than 1000 mg/L, which is approximately the level in irrigation water at which crop yield decreases. The most effective MP to accomplish this consists of a 35% reduction in WWTP effluent concentration, salt in urban return flows, salt in agricultural return flows, and road salt loading. These results point to the extreme challenge of managing salinity in the South Platte River Basin and the aggressive approaches that must be implemented to sustain irrigation practices in the basin's downstream regions. In general, this thesis provides a framework for assessing salinity movement and mitigation in a large-scale urban-agricultural river basin.